2020
DOI: 10.1016/j.jpsychires.2020.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ implementation of national guidelines with patients who self-harm

Abstract: Background National guidelines for the short-term management of self-harm are aimed at healthcare professionals who may be involved in the care of people who have self-harmed. However, evidence from small-scale studies globally suggest there is a lack of awareness of such guidelines among some groups of healthcare professionals. For the first time in a large representative sample of patient-facing healthcare professionals, we aimed to identify: (a) which healthcare professionals are aware of guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…By making the tool easier to engage with, the tool may also be useful as part of long-term support strategies, such as when the urge to self-harm may not be at their height. It is encouraging that no gender differences in acceptability were found, and thus future research could explore the extent to which brief interventions for self-harm could be delivered by health care professionals, for example, research suggests that more emphasis should be placed on improving self-harm care for patients, with a focus on improving the implementation of self-harm management guidelines [ 40 ]. One possible route is to explore the use of the VHS alongside GP care, given that the recognition of primary care is an important place to potentially help people reduce repeat self-harm [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…By making the tool easier to engage with, the tool may also be useful as part of long-term support strategies, such as when the urge to self-harm may not be at their height. It is encouraging that no gender differences in acceptability were found, and thus future research could explore the extent to which brief interventions for self-harm could be delivered by health care professionals, for example, research suggests that more emphasis should be placed on improving self-harm care for patients, with a focus on improving the implementation of self-harm management guidelines [ 40 ]. One possible route is to explore the use of the VHS alongside GP care, given that the recognition of primary care is an important place to potentially help people reduce repeat self-harm [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current national clinical guidance on management of self-harm recommends psychosocial assessment should be offered to all individuals each time they present at hospital after self-harm (2, 6). However, there is evidence of great variation in receipt of assessment in English hospitals (7, 8, 33). While studies have not been designed to evaluate the effectiveness of psychosocial assessment alone, some studies have suggested that assessment may be associated with reduced future risk of hospital-presenting self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial assessment is recommended for all hospital presenting self-harm in England (2, 6). On average around 50-60% of people presenting to accident and emergency (A&E) departments with self-harm receive a full psychosocial assessment, although this proportion varies across sites (7, 8). This clinical procedure, typically carried out by psychiatric liaison staff, includes assessing patients’ problems, mental state, risk factors and needs, and arranging appropriate aftercare.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a decrease in the number of visits so that medical personnel can take turns working (Roncero et al, 2020). Leather et al, (2020) developed internal training protocols for staff, training recommendations based on the Competency Suicide and Suicide Prevention Framework providing the gold standard for resource development. They were also recommending refresher training for professionals who rarely encounter self-injurious patients and to change the behaviour of health workers (Leather et al, 2020).…”
Section: Provider Perspectivesmentioning
confidence: 99%
“…Leather et al, (2020) developed internal training protocols for staff, training recommendations based on the Competency Suicide and Suicide Prevention Framework providing the gold standard for resource development. They were also recommending refresher training for professionals who rarely encounter self-injurious patients and to change the behaviour of health workers (Leather et al, 2020). Staff in emergency departments should learn more about mental health care, screening patients for suicidal intent, especially among children with prior emotional/behavioural problems (McBride, 2020) so that they are trained to detect early warning symptoms (Chevance et al al., 2020).…”
Section: Provider Perspectivesmentioning
confidence: 99%